A Systematic Literature Review: The Influence of AR Applications in Teaching the Human Respiratory System Scientific Literacy in Elementary Schools (2020-2025) - Mar’atun Sholeha; Tri Astuti; Bambang Subali; Arif Widiyatmoko (FKIP - Universitas Riau, 2026)
One of the major challenges in elementary science education is students’ difficulty in comprehending abstract concepts due to the underutilization of interactive visual media. This issue is particularly evident in teaching the human respiratory system, which requires three-dimensional visualization to facilitate conceptual understanding and promote scientific literacy. Therefore, this study aims to examine the influence of Augmented Reality (AR) applications on elementary school students’ scientific literacy within this topic. Adhering to PRISMA guidelines, this Systematic Literature Review (SLR) retrieved literature from Publish or Perish, Open Knowledge Maps, and Google Scholar. From an initial pool of 600 publications, a rigorous screening and critical appraisal process yielded 34 eligible articles, with 15 selected for in-depth synthesis. The findings indicate that AR applications consistently enhance students’ scientific literacy by improving conceptual understanding, visualizing abstract science concepts through interactive 3D representations, increasing learning motivation, and supporting meaningful learning experiences. In conclusion, AR represents a promising instructional innovation that provides substantial potential to strengthen scientific literacy and support digital technology integration in 21st-century elementary science education.